Minimum patterns of initial assistance given on the toxicological emergency to approach a poisoned child - Erika Okuda Tavares; Magda Lúcia Félix de Oliveira (Rev Rene)
The present study aimed at presenting the minimum patterns of initial assistance to be given to poisoned children in an emergency room of a University Hospital. The construction of the minimum patterns the module IV Initial Assistance to the Poisoned Patient, from the Course of Toxicology promoted by the National Agency of Sanitary Surveillance (ANVISA), documents and technician-scientific literature about the theme, and the authors' experience in a center of toxicological information were used as a guideline. The minimum pattern comprised the structure and the assistance process. One of the limitations found here was the inexistence of consistent references regarding the initial assistance to the poisoned; however it is believed that the established patterns in this study can contribute for the initial assistance to poisoned and their families in emergency room units.